1998
DOI: 10.1002/(sici)1098-2795(199802)49:2<176::aid-mrd8>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosyl-phosphorylated proteins are involved in regulation of meiosis in the rat egg

Abstract: Fertilization in invertebrates results in tyrosine (Tyr) phosphorylation of several egg proteins. However, the involvement of Tyr phosphorylation in mediating mammalian egg activation has not yet been investigated. Using an antibody specific for phosphotyrosine (P‐Tyr), immunoblotting, and densitometric analysis, we found that maturation of the oocyte is accompanied by a generalized increase in the P‐Tyr content of almost all egg proteins detected. After sperm penetration, 5 of the 17 protein bands detected de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 56 publications
0
13
2
Order By: Relevance
“…1, 2, 3 and 4). This disagrees with previous studies showing no change in overall levels of pTyr proteins between GV and MII [16]. Interestingly, a recent study examining changes in protein phosphorylation and the kinome of porcine oocytes during maturation found that the number of tyrosine phosphorylated proteins increased was equal to the number that decreased during transitions from GV-MI and MI-MII [22].…”
Section: Intracellular Localization and Dynamics Of Protein Phosphorycontrasting
confidence: 99%
See 1 more Smart Citation
“…1, 2, 3 and 4). This disagrees with previous studies showing no change in overall levels of pTyr proteins between GV and MII [16]. Interestingly, a recent study examining changes in protein phosphorylation and the kinome of porcine oocytes during maturation found that the number of tyrosine phosphorylated proteins increased was equal to the number that decreased during transitions from GV-MI and MI-MII [22].…”
Section: Intracellular Localization and Dynamics Of Protein Phosphorycontrasting
confidence: 99%
“…To reinitiate the meiotic cell cycle PKA migrates from the cytoplasm to the mitochondrial membrane where it is sequestered by one of the many forms of A-Kinase anchoring proteins (AKAP1) [15]. And as mentioned above, tyrosine kinase activity has recently been shown to increase significantly following fertilization [16] but the origins of these changes during meiotic maturation have not been rigorously studied. Thus, the importance of kinase regionalization and the lack of information on the relative contributions of tyr or ser/thr kinases has prompted this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Germinal vesicle (GV) oocytes were isolated from ovaries of untreated mice into M2 medium [36] supplemented with 1 μM milrinone (Sigma) to prevent resumption of meiosis and maintain the oocytes at the GV stage [37]. Oocytes arrested at metaphase of the second meiotic division (MII): Female mice were injected with 7 IU of hCG, 48 h after administration of 5 IU PMSG.…”
Section: Oocytesmentioning
confidence: 99%
“…Lysis buffer was added to samples of 300 MII eggs collected in 5-10 ml of TH medium (Ben-Yosef et al 1998). After two cycles of freezing/thawing, the extracts were stored at K70 8C.…”
Section: Western Blot Analysismentioning
confidence: 99%